2019
DOI: 10.1021/acs.inorgchem.8b03208
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis and Up-Conversion Properties of SHG-Active α-(La, Er)(IO3)3 Nanocrystals

Abstract: Pure α-La(IO 3 ) 3 and α-La 0.85 Er 0.15 (IO 3 ) 3 nanocrystals were synthesized by a microwave-assisted hydrothermal method leading to a reaction yield of 87 ± 4%. Electron microscopy and dynamic light scattering characterizations provide evidence for the formation of nanocrystals with an average size of 45 ± 10 nm for α-La(IO 3 ) 3 and 55 ± 10 nm for α-La 0.85 Er 0.15 (IO 3 ) 3 . When dispersed in ethylene glycol, the nanocrystal suspensions exhibit second-harmonic generation under near-infrared excitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Acentric α-La(IO3)3 is known for its SHG activity as initially demonstrated from comparative micron-sized powder experiments. 17,18 Recently, we reported the synthesis of α-La(IO3)3 nanocrystals and the quantitative assessment of its orientation-averaged SHG efficiency 19 that was found comparable to the other HNPs of interest (KTP, BaTiO3, LiNbO3, etc). 20,21 We also evidenced the possibility of doping α-La(IO3)3 nanocrystals with Er 3+ ions by La 3+ substitution and showed that Er 3+ -doped α-La(IO3)3 nanocrystals emit both UC-PL and SHG signals under 800-nm and 980-nm excitations.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Acentric α-La(IO3)3 is known for its SHG activity as initially demonstrated from comparative micron-sized powder experiments. 17,18 Recently, we reported the synthesis of α-La(IO3)3 nanocrystals and the quantitative assessment of its orientation-averaged SHG efficiency 19 that was found comparable to the other HNPs of interest (KTP, BaTiO3, LiNbO3, etc). 20,21 We also evidenced the possibility of doping α-La(IO3)3 nanocrystals with Er 3+ ions by La 3+ substitution and showed that Er 3+ -doped α-La(IO3)3 nanocrystals emit both UC-PL and SHG signals under 800-nm and 980-nm excitations.…”
Section: Introductionmentioning
confidence: 86%
“…α-La1-y-xYbyErx(IO3)3 nanocrystals, with y = 0.1 and x = 0.005, 0.01 and 0.02, were synthesized using a microwave-assisted hydrothermal method, as reported in [19]. In the following, the nanocrystals will be referred to as α-La0.9-xYb0.1Erx(IO3)3.…”
Section: Synthesis Of α-La1-y-xybyerx(io3)3 Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, with such a synthesis method, the α-La(IO 3 ) 3 phase crystallizes as nanocrystals (Figure S5), which could be used as nanoprobes in bio-imaging. 28 Hereafter we explore phase transformation in solid state or in hydrothermal conditions, with the goal of obtaining α-La(IO 3 ) 3 from other lanthanum iodate compounds.…”
Section: Crystallization Of Lanthanum Iodates In Solution Under Hydrmentioning
confidence: 99%
“…20,21 This is particularly the case for lanthanum iodates: according to the synthesis conditions (temperature, pH, concentration, :IO 3 molar ratio of 1:3 and heated at 250°C. 28 In the latter case, microwave heating was selected for its rapid heating rates, 29,30,31 with the idea of decoupling the nucleation and growth stages, an essential procedure to obtain homogeneous and size-controlled nanocrystals for bio-imaging applications. Indeed, acentric α-La(IO 3 ) 3 nanocrystals, also called harmonic nanoparticles (HNP), could be used as bio-labelling nanoprobes like BaTiO 3 32 or KTiOPO 4 33 nanocrystals as they can be excited in the three biological transparency windows, circumventing the limitations (low penetration depth, photobleaching, blinking, optically resonant conditions, …) encountered with most fluorescent probes.…”
Section: Introductionmentioning
confidence: 99%